VACCIMEL, an allogeneic melanoma vaccine, efficiently triggers T cell immune responses against neoantigens and alloantigens, as well as against tumor-associated antigens - Carri, Ibel; Schwab, Erika; Trivino, Juan Carlos; von Euw, Erika M.; Nielsen, Morten; Mordoh, José; Barrio, María Marcela (Frontiers in Immunology, 2025)
VACCIMEL is a therapeutic cancer vaccine composed of four irradiated allogeneic human melanoma cell lines rationally selected to cover a wide range of melanoma tumor-associated antigens (TAA). We previously demonstrated that vaccination in the adjuvant setting prolonged the distant-metastasis-free survival of cutaneous melanoma patients and that T cells reactive to TAA and the patient’s private neoantigens increased during treatment. However, immune responses directed to vaccine antigens that may arise from VACCIMEL’s somatic mutations and human polymorphisms remain unexplored. To study these immunogens, we performed whole-exome sequencing of paired tumor and germinal samples from four vaccinated patients and the vaccine cells. VACCIMEL variants were called by comparing the vaccine and the patient’s exomes, and non-synonymous coding variants were used to predict T cell epitopes. Candidates were ranked based on their mRNA expression in VACCIMEL, predicted peptide-HLA (pHLA) presentation, and pHLA stability. Then, the immune responses to prioritized epitope candidates were tested using IFNγ ELISpot assays on vaccinated patients’ PBMC samples. The comparison of the vaccine with the patients’ germinal exomes revealed on average 9481 coding non-synonymous variants, suggesting that VACCIMEL offers a high number of potential antigens. Between 0,05 and 0,2% of these variants were also found in the tumors of three vaccinated patients; however, one patient with a high tumor mutational burden (TMB) shared 19,5% somatic variants. The assessment of T cell responses showed that vaccinated patients mounted highly diverse responses against VACCIMEL peptides. Notably, effector T cells targeting the patient’s tumor antigens, comprising neoantigens and TAA, were found in higher frequencies than T cells targeting VACCIMEL-exclusive antigens. On the other hand, we observed that the immunogenic epitopes are not conserved across patients, despite sharing HLA and that immune responses fluctuate over time. Finally, a positive correlation between VACCIMEL antigen expression and the intensity of the T cell responses was found. Our results demonstrate that the immune system simultaneously responds to a high number of antigens, either vaccinal or private, proving that immune responses against epitopes not expressed in the patient’s tumors were not detrimental to the immune recognition of neoantigens and TAA.